Penatalaksanaan Fisioterapi Dengan Infra Red Dan Chest Physiotherapy Pada Asma Bronchiale - Innandita Pertiwi; Suci Amanati (Lembaga Pengembangan Kinerja Dosen, 2025)
Asthma is a non-communicable lung disease, with symptoms such as shortness of breath, wheezing and repeated coughing. Attacks can last for only a few minutes, hours, days or up to several weeks. The therapy given in this case using Infra red aims to relax the respiratory muscles and also improve blood circulation. Chest physiotherapy includes a nebulizer which aims to deliver drugs in the form of gas that can be inhaled by the patient's respiratory tract. Postural Drainage aims to drain mucus from various segments in the lungs to the larger airways with the help of gravity. Tappotement aims to divert sputum from the lungs. Works This Scientific Writing is a case study, raising patient cases and collecting data through the physiotherapy process. The modality provided is Infra red and Chest physiotherapy. The results showed significant improvements after six therapy sessions. Cough intensity decreased from frequent to no cough, while shortness of breath reduced from moderate to none. Auscultation revealed that wheezing and ronchi sounds, initially present in both lungs, eventually disappeared. Additionally, thoracic expansion improved, and the respiratory rate, initially 32 breaths per minute, decreased to 24 breaths per minute, approaching normal levels. In conclusion the combination of Infrared therapy and Chest physiotherapy is effective in managing Bronchial Asthma, particularly in reducing sputum production, improving thoracic expansion, and normalizing breathing patterns. This therapy can serve as a supportive approach in pediatric physiotherapy for respiratory disorders caused by inflammation and mucus accumulation.